Comparative Practices Literature, Language, and Culture in Britain's Long Eighteenth Century - Böhm-Schnitker, Nadine; Hartner, Marcus (Edition Kulturwissenschaft, 2022)
Comparisons not only prove fundamental in the epistemological foundation of modernity (Foucault, Luhmann), but they fulfil a central function in social life and the production of art. Taking a cue from the Practice Turn in sociology, the contributors are investigating the role of comparative practices in the formation of eighteenth-century literature and culture. The book conceives of social practices of comparing as being entrenched in networks of circulation of bodies, artefacts, discourses, and ideas, and aims to investigate how such practices ordered and changed British literature and culture during the long eighteenth century.